High-performance environment-friendly synchronous grouting material and preparation method thereof
By using fine sand containing mud and compounding various materials in the synchronous grouting materials, the problems of long settling time and poor anti-seepage ability in the prior art are solved, and efficient and environmentally friendly synchronous grouting materials are achieved, which significantly improves construction safety and economy.
Patent Information
- Application Number
- CN202510279030.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-11
AI Technical Summary
The existing synchronous grouting materials have long settling time, poor seepage resistance, high construction safety risks, and poor economic and environmental protection. Especially in coastal areas and undersea tunnel construction, there are problems such as steel bar corrosion and concrete structure bearing capacity reduction.
Fine sand containing mud powder is used to replace bentonite and fine sand, and materials such as cement, slag, iron sulfide, graphene oxide are compounded. Through the synergistic action of each component, a synergistic grouting material with excellent impermeability and compressive strength is prepared.
The short settling time, strong compressive strength and high permeability of the slurry are achieved, the amount of cement is reduced, the economic and social benefits are significantly improved, and environmental pollution is reduced.
Smart Images

Figure CN119797868A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of synchronous grouting, and more specifically, to a high-performance, environment-friendly synchronous grouting material and a preparation method thereof. Background Art
[0002] Synchronous grouting technology is an indispensable and key auxiliary method in shield tunneling. Synchronous grouting in shield excavation is an effective means to fill the construction gap between the segment lining and the stratum and reduce the subsequent soil deformation. It can enhance the stability of the tunnel and is the key to controlling surface settlement.
[0003] The synchronous grouting slurry is generally cement mortar, which is made of cement, sand, fly ash, bentonite and water in a certain proportion. However, the output of shield slag in urban subway construction is extremely abundant. If these resources can be effectively used to prepare synchronous grouting materials, it will produce huge economic, environmental and social benefits.
[0004] At present, there are a series of problems in the technology of simultaneous grouting materials for slag preparation at home and abroad: First, the original slag obtained from shield excavation is generally used as raw material. The original slag has poor grading and more coarse particles. The prepared slurry has the problem of stratified precipitation or pipe blocking during transportation. During grouting, the wall of the pipe segment may not be fully filled. At the same time, the amount of cement and other cementitious materials is still large, and the economy and environmental protection are poor. Second, the slurry coagulation time is long (generally more than 15 hours), and the slurry is in a fluid state for a long time, so that the buoyancy of the pipe segment is greater than its own gravity, which causes the pipe segment to float. Third, the slurry has poor anti-seepage ability and the pipe segment has serious water leakage. It is difficult to control the quality and the construction safety risk is high. Fourth, the shield slag in coastal areas and submarine tunnels contains a large amount of chloride ions and sulfate ions. Chloride ions will accelerate the corrosion of steel bars and cause concrete cracking; sulfate ions will corrode the tunnel lining concrete and reduce its structural bearing capacity.
[0005] Therefore, it is of great significance to develop a synchronous grouting material with strong anti-seepage ability, controllable setting time and strength, and economic and environmental protection. Summary of the invention
[0006] In view of the above technical problems, the present invention innovatively adopts mud-containing fine sand as raw material to replace the bentonite and fine sand in the original synchronous grouting material, and compound cement, slag, iron sulfide, graphene oxide and other materials. The synergistic effect between the components makes the prepared synchronous grouting material have excellent impermeability and compressive strength, and short setting time, low carbon and environmental protection, with high economic and social benefits.
[0007] In order to achieve the above object, the technical solution of the present invention is as follows: A high-performance environmentally friendly synchronous grouting material, comprising the following components by weight: 10-15 parts cement 15-20 parts of slag 20-30 parts of steel slag 300-320 parts of fine sand containing mud Iron sulfide 0.075-0.1 parts Graphene oxide 0.05-0.12 parts N,N-diisopropylformamide 0.03-0.09 parts 45-50 parts of water.
[0008] In some embodiments, the cement is ordinary Portland cement and / or sulfoaluminate cement; specifically, the ordinary Portland cement includes PO52.5 cement, PO42.5 cement, PO52.5R cement, and PO42.5R cement.
[0009] In some embodiments, the density of the slag is 2.5-3.0 g / cm 3 , with a specific surface area of 370-480m 2 / kg.
[0010] In some embodiments, the fineness of the steel slag is 200-300 mesh and the density is 3.0-3.5 g / cm 3 , 28d activity value is 95%~96%.
[0011] In some embodiments, the particle size of the mud-containing fine sand is ≤20 μm, and the clay content is 15-25%.
[0012] In some embodiments, the mud-containing fine sand is obtained by multi-stage screening of shield slag.
[0013] In some embodiments, the method for screening shield slag to obtain mud-containing fine sand comprises the following steps: (1) The slurry of the slurry shield is transported from the tunnel to the vibrating screen of the water treatment equipment to separate the sand-containing slurry of 3-6 mm; (2) the sand-containing mud obtained in step (1) is fed into a primary cyclone for separation to obtain sand-containing mud with a particle size of less than 74 μm; (3) The sand-containing mud with a particle size of less than 74 μm is fed into the secondary cyclone to separate the mud-containing fine sand with a particle size of less than 20 μm.
[0014] The present invention also provides a method for preparing shield slag according to any of the above embodiments, the method comprising the following steps: S1, mixing cement, slag, mud-containing fine sand and part of water to obtain a first slurry; S2, adding steel slag and iron sulfide to the first slurry, and then adding part of water to mix evenly to obtain a second slurry; S3, adding graphene oxide to part of the water, mixing, and then adding to the second slurry to obtain a third slurry; S4. Add N,N-diisopropylformamide to the remaining water, mix well, and add to the third slurry to obtain the high-performance environmentally friendly synchronous grouting material.
[0015] In some embodiments, in step S1, the stirring time is 1-3 min.
[0016] In some embodiments, in step S2, the stirring time is 0.5-2 min.
[0017] In some embodiments, in step S3, the stirring time is 1-3 min.
[0018] In some embodiments, in step S4, the stirring time is 1-3 min.
[0019] In some embodiments, the total stirring time in step S1 to step S4 is controlled to be 6-8 minutes.
[0020] In the technical solution of the present invention, the principle of interaction between the components is as follows: 1. The particle size distribution and particle size distribution of mud-containing fine sand are as follows: Figure 1 and Figure 2 As shown, the muddy fine sand contains a large amount of chloride ions and sulfate ions, which can react with other components, and the iron sulfide, fine sand and steel slag can react to solidify the chloride ions in the muddy fine sand and stimulate the activity of the steel slag. Cement hydration produces a large amount of calcium hydroxide: 2(3CaO·SiO2) + 6H2O = 3CaO·SiO2·3H2O + 3Ca(OH)2 2(2CaO·SiO2) + 4H2O = 3CaO·SiO2·3H2O + Ca(OH) 2 3CaO·Al2O3 + 6H2O = 3CaO·Al2O 3· 6H2O 3CaO·Al2O3·6H2O+3(Ca2SO4·2H2O)+19H2O = 3CaO·Al2O3·3Ca2SO4·31H2O 4CaO·Al2O3·Fe2O3 + 7H2O = 3CaO·Al2O3·6H2O + CaO·Fe2O3·H2O; Iron sulfide (Fe2S3) reacts with calcium hydroxide produced by cement hydration and chloride ions in muddy fine sand to produce calcium sulfide, iron hydroxide and calcium chloride; The main mineral components of steel slag are tricalcium silicate, dicalcium silicate, calcium olivine, calcium magnesian rhodonite, dicalcium ferrite, RO (solid solution formed by oxides of magnesium, iron and manganese, i.e. FeO, MgO and MnO), free calcium oxide (f-CaO), etc. Among them, active minerals such as tricalcium silicate (C3S), dicalcium silicate (C2S) and ferroaluminate have certain hydraulic gelling properties, and the hydration reaction is similar to that of cement clinker minerals.
[0021] At the same time, the free calcium oxide contained in the steel slag reacts with water to form calcium hydroxide, and further reacts with the sulfate ions in the mud-containing fine sand to form expansive hydration products such as gypsum and ettringite. While solidifying the sulfate ions in the fine sand, it can also compact the microstructure of the hardened body and improve its strength. The chemical reaction formula is as follows: CaO + H2O = Ca(OH)2 Ca(OH)2 + SO4 2- = CaSO4 CaSO4 + 2H2O = CaSO4·2H2O 3CaO·Al2O3·6H2O + 3(Ca2SO4·2H2O) + 19H2O = 3CaO·Al2O3·3Ca2SO4·31H2O 2. N,N-diisopropylformamide reacts with ferrous sulfide and calcium chloride to solidify the chloride ions in the muddy fine sand, promote the nucleation effect of graphene oxide, and react with Fe in steel slag and iron sulfide. 3+ A chelation reaction occurs to improve the density and impermeability of the slurry, while avoiding the risk of steel corrosion, as follows: In a strong alkaline environment, N,N-diisopropylformamide undergoes a hydrolysis reaction, and the amide bond (C=O) in the N,N-diisopropylformamide molecule is broken by water molecules to form a carboxylic acid product; under strong alkaline conditions, the carboxylic acid product undergoes a complexation reaction with ferrous sulfide and calcium chloride, and simultaneously plays the role of fixing sulfur and chlorine. The hydrolysis group of N,N-diisopropylformamide undergoes a chelation reaction with the iron ions in steel slag and iron sulfide to form a network-like Fe-diisopropylformamide chelate, which improves the density and strength of the slurry. At the same time, the hydrolysis group can also undergo a chelation reaction with the hydrated calcium alumina ferroate produced by the hydration of C4AF in the cement clinker, which promotes the early reaction rate of the slurry and improves the early strength of the hardened slurry.
[0022] 3. Graphene oxide GO acts as a nucleating agent to promote the hydration reaction rate and degree of C3S and C2S in steel slag, and improve the slurry strength. The nucleation effect of graphene oxide promotes the hydration of C3S and C2S in steel slag. The principle is as follows: Figure 3As shown in the figure, the rich functional groups grafted on the surface of GO have the effect of nucleation and template. GO forms a GO film on the surface of C3S and C2S in the steel slag through electrostatic adsorption. The GO film transfers Ca 2+ It is strongly adsorbed from the pore fluid to the channels between GO nanosheets, greatly reducing the saturation of hydration products, promoting the growth of more CSH on the surface of C3S, making the slurry structure denser, and improving the strength and impermeability; GO nanosheets have a strong adsorption capacity for water. They adsorb a large number of water molecules in the early stage of hydration, and "release" some water molecules during the diffusion control period to diffuse them into the interior and react with C3S to generate CSH with a denser structure, increase the content of high-density CSH, make the microstructure denser, refine the pore size, and improve the strength and impermeability of the hardened slurry.
[0023] The experiment showed that different amounts of graphene oxide added promoted the hydration of C3S and C2S in steel slag. Figure 4 shown.
[0024] In summary, through the synergistic effect of the various components in the present invention, the obtained synchronous grouting material can have excellent compressive strength and anti-permeability performance.
[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The mud-containing fine sand of the present invention has a good gradation and a dosage of more than 70%. Compared with traditional synchronous grouting materials, it achieves zero addition of fly ash, bentonite and fine sand, and can reduce cement consumption by 60%. The original slurry material cost of the project department is 268.67 yuan / cubic meter, and the slurry material cost of the present invention is about 60.48 yuan / cubic meter, which reduces the material cost by about 77.5%. At the same time, it also reduces the transportation and disposal costs of a large amount of slag, increases the added value of slag utilization, and has significant overall economic benefits.
[0026] (2) The new green admixture greatly improves the anti-seepage performance of the slurry through the synergistic effect with other components, reduces the setting time of the slurry, and improves the compressive strength of the slurry. The various properties of the slurry can be flexibly adjusted according to the on-site construction conditions and design requirements, and it has strong adaptability.
[0027] (3) The shield slag slurry making process adopted by the present invention is simple, has high production efficiency, and occupies a small area of equipment, and can be adapted to small urban subway construction sites.
[0028] (4) The present invention is a green and environmentally friendly grouting material that can turn slag into treasure, reduce environmental pollution caused by slag transportation and discharge, reduce natural sand and gravel mining, and reduce secondary pollution and carbon emissions. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The particle size distribution diagram of the mud-containing fine sand used in the embodiments and comparative examples of the present invention; Figure 2 XRD phase analysis diagram of mud-containing fine sand used in the embodiments and comparative examples of the present invention; Figure 3 Schematic diagram of the graphene oxide promoting hydration of steel slag; Figure 4 The electron microscope images of different graphene oxide GO addition amounts (GO mass / steel slag mass) promoting hydration of steel slag; Figure A shows the hydration of steel slag without GO doping; Figure B shows the hydration of steel slag with 0.01% GO doping; Figure C shows the hydration of steel slag with 0.02% GO doping; Figure D shows the hydration of steel slag with 0.03% GO doping; Figure 5 The fluidity test diagrams of Example 3 and Comparative Example 1 are shown in Figure A, wherein Figure A is the test diagram of Example 3, and Figure B is the test diagram of Comparative Example 1; Figure 6 The figures are the coagulation time test figures of Example 3 and Comparative Example 3; wherein, Figure A is the test figure of Example 3, and Figure B is the test figure of Comparative Example 3; Figure 7 These are compressive strength test diagrams of Example 3, Comparative Example 2, and Comparative Example 4; wherein, Figure A is a test diagram of Example 3, Figure B is a test diagram of Comparative Example 2, and Figure C is a test diagram of Comparative Example 4. DETAILED DESCRIPTION
[0030] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0032] The parameters or preparation methods of some raw materials used in the examples and comparative examples of the present invention are as follows: Cement: commercially available, PO42.5 ordinary Portland cement; Slag: Commercially available, density 2.89 g / cm 3 , with a specific surface area of 422.3m 2 / kg; Steel slag: commercially available, with a fineness of 200-300 mesh and a density of 3.0-3.5 g / cm 3 , 28d activity value 95%~96%; The fine sand containing mud is obtained from shield slag after multi-stage screening, as follows: (1) The slurry of the slurry shield is transported from the tunnel to the vibrating screen in the slurry treatment equipment, where sand-containing slurry of 3 to 6 mm is separated.
[0033] (2) Next, the sandy mud with a particle size of 3 to 6 mm enters the primary cyclone for separation to obtain sandy mud with a particle size of less than 74 μm.
[0034] (3) The sand-containing mud continues to enter the secondary cyclone to separate the mud-containing fine sand with a particle size of less than 20 μm.
[0035] Iron sulfide, graphene oxide, and N,N-diisopropylformamide were all purchased from the market.
[0036] Example 1
[0037] A high-performance environmentally friendly synchronous grouting material, comprising the following components by weight: 10 parts cement 15 parts slag 25 parts of steel slag 300 parts of fine sand containing mud Iron sulfide 0.075 parts Graphene oxide 0.05 parts 0.03 parts of N,N-diisopropylformamide 50 parts water; The preparation method comprises the following steps: (1) Using an excavator or a forklift, the mud-containing fine sand is transported to a mortar mixer, cement and slag are transported to the mixer through storage tanks, water (20 parts) is added and the mud-containing fine sand is fully mixed (both are equipped with an automatic weighing system) for 2 minutes to obtain a first slurry; (2) adding steel slag and iron sulfide to the first slurry in sequence, and then adding water (15 parts) and stirring thoroughly for 1 minute to obtain a second slurry; (3) After mixing graphene oxide with water (10 parts), add the mixture to the second slurry and stir thoroughly for 2 minutes to obtain a third slurry.
[0038] (4) Mix NN diisopropylformamide with water (5 parts), add it to the third slurry and stir thoroughly for 2 minutes to obtain a synchronous grouting material; The entire pulping process should be controlled within 6-8 minutes.
[0039] Example 2-3 The composition of the synchronous grouting material of Example 2-3 is shown in Table 1, and the preparation method is the same as that of Example 1.
[0040] Comparative Example 1 A synchronous grouting material, comprising the following components in parts by weight: 15 parts cement 20 parts of slag 20 parts of steel slag 320 parts of fine sand containing mud 0.25 parts of accelerating agent 45 parts water The preparation method comprises the following steps: (1) Using an excavator or a forklift, the mud-containing fine sand is transported to a mortar mixer, cement and slag are transported to the mixer through storage tanks, water (20 parts) is added and the mud-containing fine sand is fully mixed (both are equipped with an automatic weighing system) for 2 minutes to obtain a first slurry; (2) adding steel slag to the first slurry, and then adding water (15 parts) and stirring thoroughly for 2-3 minutes to obtain a second slurry; (3) Mix the accelerating setting agent with water (10 parts), add it to the second slurry and stir thoroughly for 2-3 minutes to obtain the third slurry, i.e., the synchronous grouting material; The entire pulping process should be controlled within 6-8 minutes.
[0041] Comparative Examples 2-4 The raw material compositions of Comparative Examples 2-4 are shown in Table 1, and the preparation methods are the same as those of Comparative Example 1.
[0042] Table 1 Ratios of raw materials in Examples and Comparative Examples
[0043] The synchronous grouting materials obtained in Examples 1-3 and Comparative Examples 1-4 were subjected to relevant performance tests, as follows: The test method for the setting time of the synchronous grouting material slurry in the embodiments and comparative examples of the present invention refers to the relevant provisions of the industry standard "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009); The fluidity test refers to the provisions of the truncated cone fluidity test in the current national standard "Technical Specifications for Application of Cement-based Grouting Materials" (GB / T50448-2015); The compressive strength test method refers to the provisions of the unconfined compressive strength test in the current industry standard "Cement-Soil Mix Design Code" (JGJ / T233-2011); The methods for determining the impermeability pressure and impermeability grade shall refer to the relevant provisions of "Standard for Test Methods for Basic Properties of Building Mortar" (JGT / T70-2009) and "Premixed Mortar" (GB / T 25181-2019).
[0044] The test results are shown in Table 2 and Figure 5-Figure 7 shown.
[0045] Table 2 Performance test results of synchronous grouting materials of embodiments and comparative examples
[0046] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0047] The above-mentioned embodiments only express several implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.
Claims
1. A high-performance environmentally friendly synchronous grouting material, characterized in that: By weight, it includes the following components: 10-15 parts cement 15-20 parts of slag 20-30 parts of steel slag 300-320 parts of fine sand containing mud Iron sulfide 0.075-0.1 parts Graphene oxide 0.05-0.12 parts N,N-diisopropylformamide 0.03-0.09 parts 45-50 parts of water.
2. The high-performance environmentally friendly synchronous grouting material according to claim 1, characterized in that: The cement is ordinary Portland cement and / or sulphoaluminate cement.
3. The high-performance environmentally friendly synchronous grouting material according to claim 1, characterized in that: The density of the slag is 2.5-3.0 g / cm 3 , with a specific surface area of 370-480m 2 / kg.
4. The high-performance environmentally friendly synchronous grouting material according to claim 1, characterized in that: The steel slag has a fineness of 200-300 mesh and a density of 3.0-3.5 g / cm 3 , 28d activity value is 95%~96%.
5. The high-performance environmentally friendly synchronous grouting material according to claim 1, characterized in that: The particle size of the mud-containing fine sand is ≤20 μm, and the clay content is 15-25%.
6. The high-performance environmentally friendly synchronous grouting material according to claim 1, characterized in that: The mud-containing fine sand is obtained after shield slag is screened at multiple levels.
7. The high-performance environmentally friendly synchronous grouting material according to claim 6, characterized in that: The method for obtaining mud-containing fine sand by screening shield slag comprises the following steps: (1) The slurry of the slurry shield is transported from the tunnel to the vibrating screen of the water treatment equipment to separate the sand-containing slurry of 3-6 mm; (2) the sand-containing mud obtained in step (1) is fed into a primary cyclone for separation to obtain sand-containing mud with a particle size of less than 74 μm; (3) The sand-containing mud with a particle size of less than 74 μm enters the secondary cyclone to separate the mud-containing fine sand with a particle size of less than 20 μm.
8. The method for preparing the high-performance environmentally friendly synchronous grouting material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing cement, slag, mud-containing fine sand and part of water to obtain a first slurry; S2, adding steel slag and iron sulfide to the first slurry, and then adding part of water to mix evenly to obtain a second slurry; S3, adding graphene oxide to part of the water, mixing, and then adding to the second slurry to obtain a third slurry; S4. Add N,N-diisopropylformamide to the remaining water, mix well, and add to the third slurry to obtain the high-performance environmentally friendly synchronous grouting material.
9. The method for preparing a high-performance, environmentally friendly synchronous grouting material according to claim 8, characterized in that: In step S1, the stirring time is 1-3 min; and / or, in step S2, the stirring time is 0.5-2 min; and / or, in step S3, the stirring time is 1-3 min; and / or, in step S4, the stirring time is 1-3 min.
10. The method for preparing a high-performance environmentally friendly synchronous grouting material according to claim 9, characterized in that: The total stirring time in step S1 to step S4 is controlled at 6-8 min.
Citation Information
Patent Citations
Vibration-resistant high-toughness shield tunnel synchronous grouting material and preparation method thereof
CN115872676A
Gelling material for synchronous grouting, synchronous grouting material and preparation method
CN116639893A
Fractured rock mass grouting reinforcement material used in high ground temperature environment and application of fractured rock mass grouting reinforcement material
CN118239743A
Synchronous grouting material based on muddy silt shield muck and preparation method thereof
CN119462024A
Cement treatment agent and treatment method
JP2002003253A